2021
DOI: 10.1111/jgs.17607
|View full text |Cite
|
Sign up to set email alerts
|

Can changes in social contact (frequency and mode) mitigate low mood before and during the COVID‐19 pandemic? The I‐CONECT project

Abstract: Background/Objectives: The coronavirus disease 2019 (COVID-19) global outbreak allowed a natural experiment to observe how older adults changed social patterns and how it affected their emotional well-being. We studied the frequency and modes of social contact and their effects on older adults' mood before and during the COVID-19 pandemic. Design: Phone-based surveys were administered weekly before and during the COVID-19 pandemic. Setting: Participants were recruited from Portland, Oregon, and Detroit, Michig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…We found that the contact frequency with family members, relatives, or colleagues did not significantly differ across the two time points, but connecting with close friends, schoolmates, and religious members was less frequent during the pandemic than before. These findings were consistent with the report in other countries that social connections with family were more or less similar between the pre- and during the pandemic whereas social connections with friends were significantly lower after the pandemic [ 67 , 68 ]. A relationship with close friends or schoolmates is one of the most private connections, which involves personal and emotional proximity and functions as an essential resource for physical and mental health [ 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the contact frequency with family members, relatives, or colleagues did not significantly differ across the two time points, but connecting with close friends, schoolmates, and religious members was less frequent during the pandemic than before. These findings were consistent with the report in other countries that social connections with family were more or less similar between the pre- and during the pandemic whereas social connections with friends were significantly lower after the pandemic [ 67 , 68 ]. A relationship with close friends or schoolmates is one of the most private connections, which involves personal and emotional proximity and functions as an essential resource for physical and mental health [ 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…We add to extant literature showing how Veterans maintained social interactions through letter writing or using virtual platforms to connect with friends and family and coped by taking up new hobbies, spending more time outdoors, or using the increased alone time for self-reflection. 1 , 25 - 28 Veterans in the current study expressed a willingness to learn about new technology, especially if it helped them connect with friends and family.…”
Section: Discussionmentioning
confidence: 94%
“…47,48 home care recipients with limited social resources would likely benefit from strategies to prevent further decline in mood. A study by Wu et al 51 found that writing to friends and increasing in-person family time were 2 social interventions that showed promise for mitigating low mood for older adults with limited social resources.…”
Section: Discussionmentioning
confidence: 99%